Direct-to-consumer testing as consumer initiated testing: compromises to the testing process and opportunities for quality improvement: an opinion paper from the EFLM DTCT-Taskforce : opinion paper - Shih, Patti; Sandberg, Sverre; Balla, Jan; Basok, Banu Isbilen; Brady, Jennifer J.; Croal, Bernard; Vos, Nathalie De; Karlsson, Mathias; Kedars, Piret; Ozben, Tomris; Pijanovic, Marina; Plebani, Mario; et al. (Clinical chemistry and laboratory medicine, 2025)
Direct-to-consumer testing (DTCT) refers to commercial laboratory tests initiated by laypersons without the involvement of healthcare professionals. As this market grows in size and variety of products, a clear definition of DTCT to ground the conceptualization of their harms and benefits is needed. We describe how three different modalities of DTCT (home self-testing, self-sampled tests, and direct access tests) present caveats to the traditional testing process (‘brain-to-brain loop’), and how this might differ between medical vs. non-medical laboratories. We make recommendations for ways to improve quality and reduce errors with respect to DTCT. The potential benefits and harms of DTCT will invariably depend on the context and situation of individual consumers and the types of tests involved. Importantly, implications for both consumers and the healthcare system should be considered, such as the effects on improving health outcomes and reducing unnecessary testing and use of clinical resources. ‘Consumer initiation’ must be a central defining characteristic of DTCT, to clearly demarcate the key drawbacks as well as opportunities of this type of testing from a laboratory specialists’ perspective. The concept of ‘consumer initiated testing’ should also help define DTCT regulation, and provide a locus of efforts to support consumers as the main decision-makers in the purchasing and conducting of these tests in the absence of clinician gatekeeping.
Online veröffentlicht: 14. August 2024
Gesehen am 11.11.2024